Identification of Needs for Application-Assisted Continuity of Care for Preconception Woman at Risk Planning Pregnancy in Sleman Regency - Eka Vicky Yulivantina; Maryudela Afrida Afrida; Yudha Christianto Firmansyah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Maternal mortality rate is key indicator of maternal and child health services. According to the World Health Organization (WHO), maternal mortality remains high. Preconception care plays a crucial role in addressing this issue, ensuring womenâ€™s health before pregnancy. Based on Continuity of Care concept, continues midwifery care during the premarital preconception period allows health workers to monitor and support women, promoting planned pregnancies under optimal conditions. This study aims to identify the need for application-based continuity of care for at-risk preconception women planning pregnancy in Sleman Regency. Using a mixed-method method approach, it combines qualitative phenomenological research with quantitative Research and Development (RD). Findings indicate that support for at risk preconception couples remains suboptimal. Although there is collaboration between health workers and Religious Affairs Offices, further optimization is needed to enhance awareness and monitoring. To address this gap, the MEMBUMI SEHAT application was developed to provide integrated services, offering comprehensive medical information and recommendations. This tool aims to improve continuity of care, reducing complication for both the mother and fetus. The study highlights the importance of implementing health policies that prepare couples for pregnancy. The MEMBUMI SEHAT app is feasible for supporting at-risk preconception couples by providing continuous, accessible, and informative care.Â